Assessing Students' Higher-Order Thinking Skills: Knowledge and Practices of Chemistry Teachers in Vocational Senior Secondary Schools - Elin Driana; Ary Susilowati; Ernawati Ernawati; Abd. Rahman A. Ghani (Jurnal Pendidikan Teknologi dan Kejuruan, 2021)
The success of efforts in developing students' higher-order thinking skills (HOTS) to face the complex challenges in the 21st century also depends on how teachers implement classroom assessments. Studies on teachers' knowledge and practices have been conducted at different levels of education. However, studies that involved teachers in vocational senior secondary schools are still limited. Therefore, this qualitative study aimed at exploring chemistry teachers' knowledge of HOTS, their assessment practices, and the barriers encountered. Ten chemistry teachers from three public and six private vocational senior secondary schools in South Jakarta were involved in this study. Data were collected through semi-structured interviews conducted between August and September 2019. The findings revealed that almost all chemistry teachers believed that providing students in vocational senior secondary schools with HOTS was essential. However, knowledge of HOTS among most teachers was still inadequate, contributing to their unpreparedness in assessing the skills. Misunderstanding about higher-order thinking was also revealed, such as associating higher-order thinking with item difficulties. The teachers in this study considered students' factors as barriers in cultivating HOTS in chemistry learning in vocational senior secondary schools, such as lack of motivation, low academic ability, and lack of reading habits. The teachers also mentioned the shortage of facilities as another barrier that inhibited their efforts in fostering HOTS in chemistry learning. Proper teacher professional development programs are needed to increase teachers' understanding of HOTS assessment and help them develop various strategies for fostering HOTS among vocational senior secondary school students.